The Fate of Foreign Languages Compared to Indigenous Languages in Post-Colonial Africa - Hbaiz,Mostafa; Korichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2019)
This study was based on comparison between indigenous languages and imported languages in three fields: politics, society and economics, for the purpose of predicting the languages of the future in Africa. In this research, concepts such as imported languages, foreign languages, excolonizers' languages and former masters' languages all were used to refer to the western languages that were inherited from the colonial rule. Meanwhile, concepts which fell in line with mother tongues, indigenous languages, local languages and native languages refer to languages originated in Africa or have a long history in the continent such as Arabic. The aim of this research was to show the fate of imported languages and indigenous languages, based on a comparative study of the impacts of both, on the three above mentioned fields. Hence, this thesis highlighted the main contributions done by various literary works that aimed to vindicate local languages on the African continent. To this end, it was hypothesized that factors in fields of politics, society and economy are leading to the decline of foreign languages while raising the status of indigenous languages. In that, African local languages provide more benefits, compared to foreign languages that are doing more harm. Accordingly, it is possible that the future of foreign languages will be dethroned, and indigenous languages will shape the future of Africa. Results obtained, hence, confirmed that foreign languages hold status because of their control over local African language policies while society remains an eternal domain of local African languages. Yet, in the field of economics, indigenous languages are rising to power due to their tremendous benefits